2018
DOI: 10.1002/brb3.936
|View full text |Cite
|
Sign up to set email alerts
|

Serum vitamin D in patients with mild cognitive impairment and Alzheimer's disease

Abstract: ObjectivesTo determine the relevance of Mini‐Mental State Examination (MMSE), serum 25‐hydroxyvitamin D (25(OH)D3), and 1,25(OH)2D3 concentrations to mild cognitive impairment (MCI) and various stages of Alzheimer's disease (AD).Materials and MethodsThe study included 230 participants (>74 years) allocated to three main groups: 1‐healthy subjects (HS, n = 61), 2‐patients with MCI (n = 61), and 3‐ patients with Alzheimer's disease (AD) subdivided into three stages: mild (n = 41), moderate (n = 35), and severe A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 58 publications
4
28
0
Order By: Relevance
“…Our result is consistent with a large volume of published studies that have found an association between MMSE score and serum vitamin D (Balion et al, 2012;Matchar et al, 2016;Vedak et al, 2015). A recent study purports the combination of MMSE score with serum 25-OHD could have a predictive value of 98% in diagnosing MCI and AD (Ouma et al, 2018). Similarly, in elderly MCI patients, hippocampal atrophy is predictive of progression to AD (Jack Jr. et al, 1999).…”
Section: Serum Vitamin D As a Potential Biomarkersupporting
confidence: 91%
See 1 more Smart Citation
“…Our result is consistent with a large volume of published studies that have found an association between MMSE score and serum vitamin D (Balion et al, 2012;Matchar et al, 2016;Vedak et al, 2015). A recent study purports the combination of MMSE score with serum 25-OHD could have a predictive value of 98% in diagnosing MCI and AD (Ouma et al, 2018). Similarly, in elderly MCI patients, hippocampal atrophy is predictive of progression to AD (Jack Jr. et al, 1999).…”
Section: Serum Vitamin D As a Potential Biomarkersupporting
confidence: 91%
“…In this study, there were significant differences in all cognitive scales (MMSE, CDR, CDR-SOB, and GDS) except the GDepS between the vitamin D-deficient and not-deficient groups. A recent study purports the combination of MMSE score with serum 25-OHD could have a predictive value of 98% in diagnosing MCI and AD (Ouma et al, 2018). A recent study purports the combination of MMSE score with serum 25-OHD could have a predictive value of 98% in diagnosing MCI and AD (Ouma et al, 2018).…”
Section: Serum Vitamin D As a Potential Biomarkermentioning
confidence: 99%
“…Recently, it has been shown that serum vitamin D was lower in MCI and various stages of Alzheimer’s disease. Accordingly, vitamin D status could be treated as a useful biomarker for predicting and diagnosing MCI and Alzheimer disease [ 60 ]. This is in line with the results of a former study that indicated a positive association between MMSE test results and vitamin D concentration [ 61 ], although no correlation between MMSE and vitamin B12 levels has been observed.…”
Section: Discussionmentioning
confidence: 99%
“…For cognitive function, low levels of 25(OH)D is correlate with increased risk of cognitive impairments. furthermore, vitamin D has a vital role in healthy brain function and de ciency of vitamin D may lead to cognitive impairment (28) and vitamin D supplements improved cognitive function in various medical papulations (29,30). Also, mindfulness by affecting on dlpfc, amygdala, PFC and limbic system, has revealed improvements in cognitive functions (i.e., executive function, working memory and attention ) in younger and older patients (25).…”
Section: Resultsmentioning
confidence: 99%